Symptoms and Characteristics of Family Intensive Care Unit Syndrome among Families of Critically III Patients: A Scoping Review - Dwi Cahyarani; Suhartini Ismail; Wahyu Hidayati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Family Intensive Care Unit Syndrome (FICUS) is a cluster of psychological, emotional, and physical symptoms experienced by family members of critically ill patients in response to prolonged stress, medical uncertainty, and the burden of decision-making during ICU care. Although research exploring this condition has grown in recent years, available evidence remains fragmented, highlighting the need for a comprehensive synthesis of symptom manifestations, risk factors, and emerging patterns across studies and contexts. This scoping review aimed to map the symptoms of FICUS systematically reported in the literature over the past 10 years and to identify key characteristics and thematic patterns emerging across various research designs and contexts. This study followed the methodological framework of Arksey and O’Malley, refined by Levac et al., and was reported according to PRISMA-ScR guidelines. A comprehensive search was conducted across five databases (PubMed, Scopus, ScienceDirect, CINAHL, and ProQuest) using a combination of keywords and MeSH terms related to ICU, critically ill patients’ families, psychological distress, and FICUS symptoms. The search was limited to full-text articles published in the last ten years (2015-2025) in English or Indonesian. Of 2,977 identified records, 1,240 duplicates were removed. A total of 1,737 titles and abstracts were screened, 184 full texts were reviewed, and 15 studies met the inclusion criteria. Data were extracted and analyzed using thematic narrative synthesis. FICUS symptoms were categorized into three domains: psychological (anxiety, depression, PTSD), emotional (sadness, anger, worry, psychological threat), and somatic/functional (sleep disturbance, fatigue, impaired concentration). Anxiety and depression were the most consistently reported symptoms, while emotional constructs—such as uncertainty, role identity threat, and spiritual distress—were predominantly identified in qualitative studies. The characteristic Major risk factors included younger caregiver age, female gender, patient mortality, longer ICU stay, and poor communication quality. FICUS is a multidimensional phenomenon consistently observed across different countries and ICU care contexts. Findings highlight the urgency for routine psychological screening, improved communication strategies, and structured emotional support interventions for families of critically ill patients.